Interaction between M-CSF and IL-10 on productions of IL-12 and IL-18 and expressions of CD14, CD23, and CD64 by human monocytes - JI Xiao-hui; YAO Ting; QIN Jun-chuan; WANG Shu-kui; WANG Hui-juan; YAO Kun (Acta Pharmacologica Sinica; Vol 25, No 10 (October 2004): Acta Pharmacologica Sinica, 2016)
AIM: To Study the interaction of macrophage colony-stimulating factor (M-CSF) and interleukin-10 (IL-10) in productions of IL-12 and IL-18 and expressions of CD14, CD23, and CD64 by human monocytes. METHODS: Purified adherent human monocytes were cultured with M-CSF or IL-10 alone, or with M-CSF+IL-10 and 2-3d later, the culture supernatants and cells were separated and collected. IL-12P40 and IL-18 levels in the supernatants were determined by ELISA and the percentages of CD14, CD23, and CD64 positive cells were examined by flow cytometry. RESULTS: (1) IL-10 decreased M-CSF-induced IL-18 levels, while M-CSF further reduced IL-12P40 level in the culture supernatants of IL-10-treated monocytes; (2) IL-10 alone had no effect on the percentage of CD14-positive cells, but further increased the percentage of CD14-positive cells induced by M-CSF; M-CSF alone had no effect on the percentage of CD64-positive cells, but further increased the percentage of CD64-positive cells induced by IL-10; (3) IL-10 decreased the percentage of CD23-positive cells induced by M-CSF. CONCLUSION: Between M-CSF and IL-10, there were antagonistic effects on inducing IL-18 and CD23 expressions by monocytes; there were also synergistic effects on inhibiting IL-12P40 production and inducing CD14 and CD64 expressions by monocytes.